The Applied Research of E-commerce Technology from the Perspective of Communication Studies - Yu, Bing (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of computer network technology and information technology, the e-commerce mode is constantly innovated and applied, which has injected new vitality into the commercial activities. In terms of technology, advanced technologies such as mobile payment, artificial intelligence, big data and AR technology have been widely used in the field of e-commerce, and the innovation of e-commerce technology has also promoted the enrichment of content and diversification of information dissemination. As a subject of information communication and communication, communication science provides important theoretical support and practical guidance for the development of e-commerce technology. From the perspective of communication science, this paper discusses in-depth the innovation and application of e-commerce technology, aiming to reveal the important role of the principle of communication science in the development of e-commerce technology, and discuss how to promote the sustainable development of e-commerce industry through technological innovation and application.